2016
DOI: 10.1007/978-3-319-30737-4_41
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Mechanochemical Treatment of Cellulose on Characteristics of Nanocellulose Films

Abstract: The development of the nanomaterials with the advanced functional characteristics is a challenging task because of the growing demand in the market of the optoelectronic devices, biodegradable plastics, and materials for energy saving and energy storage. Nanocellulose is comprised of the nanosized cellulose particles, properties of which depend on characteristics of plant raw materials as well as methods of nanocellulose preparation. In this study, the effect of the mechanochemical treatment of bleached softwo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 26 publications
0
1
0
Order By: Relevance
“…Additionally, it was observed that the maximum degradation temperature of CC was higher (338 • C), compared to the produce nanofibers (LP-HUS, 306 • C), which could be attributed to the number of free terminal chains, which decompose at lower temperatures [33,34]. Hydrolysis with H 2 SO 4 caused a significant decrease in the degradation temperature and an increase in the maximum degradation temperature range for PL-HUS between 181 • C and 360 • C, caused by the inclusion of sulfate groups in the cellulose chains [33,35].…”
Section: Thermal Stability Analysismentioning
confidence: 97%
“…Additionally, it was observed that the maximum degradation temperature of CC was higher (338 • C), compared to the produce nanofibers (LP-HUS, 306 • C), which could be attributed to the number of free terminal chains, which decompose at lower temperatures [33,34]. Hydrolysis with H 2 SO 4 caused a significant decrease in the degradation temperature and an increase in the maximum degradation temperature range for PL-HUS between 181 • C and 360 • C, caused by the inclusion of sulfate groups in the cellulose chains [33,35].…”
Section: Thermal Stability Analysismentioning
confidence: 97%